The Anti-Cancer Effects of Frondoside A - Thomas E. Adrian; Peter Collin (Marine Drugs, 2018)
Frondoside A is a triterpenoid glycoside from the Atlantic Sea Cucumber, Cucumaria frondosa. Frondoside A has a broad spectrum of anti-cancer effects, including induction of cellular apoptosis, inhibition of cancer cell growth, migration, invasion, formation of metastases, and angiogenesis. In cell lines and animal models studied to date, the anti-cancer effects of the compound are seen in all solid cancers, lymphomas, and leukemias studied to date. These effects appear to be due to potent inhibition of p21-activated kinase 1 (PAK1), which is up-regulated in many cancers. In mouse models, frondoside A has synergistic effects with conventional chemotherapeutic agents, such as gemcitabine, paclitaxel, and cisplatin. Frondoside A administration is well-tolerated. No side effects have been reported and the compound has no significant effects on body weight, blood cells, or on hepatic and renal function tests after long-term administration. Frondoside A may be valuable in the treatment of malignancies, either as a single agent or in combination with other therapeutic modalities.